2002
DOI: 10.1016/s0967-0645(02)00332-6
|View full text |Cite
|
Sign up to set email alerts
|

Stable C and N isotopic composition of sinking particles and zooplankton over the southeastern Bering Sea shelf

Abstract: Stable carbon and nitrogen isotopic composition of zooplankton, suspended particulate organic matter (SPOM), and sinking particles collected using sediment traps were measured for samples obtained from the southeastern Bering Sea middle and outer shelf during 1997-1999. The quantity of material collected by the middle shelf sediment trap was greater in both spring and late summer and fall than in early and mid-summer. The d 15 N of SPOM, sinking material and zooplankton showed greater inter-annual variability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 35 publications
(49 reference statements)
3
13
2
Order By: Relevance
“…NB01 to 1.46 μmol/dm 3 at Sta. B07 with an average of (0.92±0.37) μmol/dm 3 (Table 1) Continued from Table 1 3.3 13 C POC and 15 N PN 13 C POC and 15 N PN in the Bering Sea were listed in Table 1 and plotted for all stations along the sampling transects as shown in Figs 2e and f. 13 C POC dramatically varied from −29.93‰ to −20.26‰ with an average of (−24.21±1.97)‰, comparing well with those reported in previous studies in the Bering Sea (Smith et al, 2002;Guo, Tanaka et al, 2004), but somewhat lighter than those from the western Arctic Ocean (Zhang et al, 2012). In addition, 13 C POC values in the Bering Sea were lighter than those observed in tropical, subtropical or temperate seas, such as the southwestern Indian Ocean (Francois et al, 1993), the northeastern Pacific Ocean (Wang et al, 1998) and the Bohai Bay (Gao et al, 2012).…”
Section: Poc and Pnsupporting
confidence: 83%
“…NB01 to 1.46 μmol/dm 3 at Sta. B07 with an average of (0.92±0.37) μmol/dm 3 (Table 1) Continued from Table 1 3.3 13 C POC and 15 N PN 13 C POC and 15 N PN in the Bering Sea were listed in Table 1 and plotted for all stations along the sampling transects as shown in Figs 2e and f. 13 C POC dramatically varied from −29.93‰ to −20.26‰ with an average of (−24.21±1.97)‰, comparing well with those reported in previous studies in the Bering Sea (Smith et al, 2002;Guo, Tanaka et al, 2004), but somewhat lighter than those from the western Arctic Ocean (Zhang et al, 2012). In addition, 13 C POC values in the Bering Sea were lighter than those observed in tropical, subtropical or temperate seas, such as the southwestern Indian Ocean (Francois et al, 1993), the northeastern Pacific Ocean (Wang et al, 1998) and the Bohai Bay (Gao et al, 2012).…”
Section: Poc and Pnsupporting
confidence: 83%
“…Thus the trophic level of an organism increases when coccolithophores are the main primary producers. Smith & Heinrichs (2002) also found anomalously high δ 13 C and δ 15 N values in plankton and sediment trap samples collected in 1999 compared to 1997 and 1998, which they attributed to the early and prolonged coccolithophore bloom in 1999. Schell et al (1998) concluded that assessing trophic levels of top consumers must be done cautiously, because the natural range of isotope ratios can be very large.…”
Section: Trophic Relationships Of Chrysaora Melanastermentioning
confidence: 92%
“…Topsoil-PF refers to organic matter from the active layer of permafrost, ICD-PF to relict Pleistocene Ice Complex deposit permafrost (yedoma) and marine OC to organic matter from primary production. The endmember values for different sources are taken from a dataset compiled by Vonk et al (2012) and a study by Smith et al (2002). The green arrow points to the direction from the bottom to the top of the core (GC58).…”
Section: Dual-isotope-based Source Apportionment Of Ocmentioning
confidence: 99%